Occupational stress in healthcare workers during a COVID-19 pandemic - Pinchuk , I.Y.; Pishel, V.Y.; Polyvianaia, M.Y.; Yachnik , Y.V.; Virchenko , V.V. (Medicni Perspektivi, 2021)
Healthcare workers experience overwhelming occupational and psycho-emotional stress during COVID-19 pandemic. Occupational stress leads to emotional burnout, can cause anxiety, depression and other psychopathological symptoms, influencing the quality of medical care. Existing situation necessitates to define risk factors, influencing occupational stress in healthcare workers in order to develop ways and methods to overcome it. Aim of the study was to identify socio-psychological factors associated with occupational stress in healthcare workers during the COVID-19 epidemic in Ukraine. Using a specially designed questionnaire, an online survey of 1,100 medical workers was conducted in all regions of Ukraine. Questioning was carried out over three weeks from 30.03.2020 to 21.04.2020, during the period of quarantine. The majority of respondents were female medical workers (79.9%). Age of respondents: up to 30 years – 179 (16.2%), from 31 to 60 – 824 (75.0%), over 60 – 97 (8.8%), among them doctors – 695 (63.1%) 236 nurses (21.5%), more than a third are general practitioners. Direct care for patients with COVID-19 was provided by 170 (15.5%) medical personnel. The analysis of the results of the questionnaire enabled to determine the peculiarities of medical worker`s response to the situation in connection with COVID-19 and highlight the emotional and behavioral factors associated with stress that are significant for most respondents. The study answered the questions regarding the perceived risk associated with the spread, contamination and death related to coronavirus. The most significant factors affecting the occurrence of stress in medical workers are identified. Along with this, factors contributing to stress coping have been identified as well. For subsequent statistical processing, all respondents were divided into two groups depending on the severity of the anxiety/fear. Comparison of these groups by socio-demographic indicators was done using the test χ2. There were no statistically significant differences between groups in all socio-demographic indicators, except for age. That is, only the age factor affected the severity of anxiety/fear among healthcare workers due to COVID-19 (p<0.05). Comparative analysis to assess the severity of stress in groups was performed using the Mann-Whitney U test. Healthcare workers with severe anxiety/fear have a high risk for development of occupational stress during a COVID-19 pandemic (p<0.01). In conclusion, the need for the development and implementation of methods for the prevention of occupational stress in medical workers in the current epidemic situation is substantiated.